(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In an age of technology and economics, human capital has important andaxial role in the organization and human resource accounting has a wideperception to key resources of organization i.e. human resources. Humanresources accounting is new branch of accounting that has Short-lived andgenerally deals to a range of policies and measures that are related to variousaspects of human resources and It gives importance to an organization’s mostimportant asset is its human resources and human resource management is the keyto success in an organization and to achieve this important matter must reviewand evaluation of human resources data be with knowledge of accounting based onempirical studies and methods of measurement and reporting of human resourcesaccounting information. Undoubtedly human resource management withoutinformation cannot be done and take decision and human resources accounting ispractical way to inform the decision makers who are committed to harnessinghuman resources, human resources accounting with applying accountingprinciples in the organization and is with conducting basic research on theextent of the of human resources accounting information” effect of employees’personal performance.